Banish the literate city, displace the root. Poetics and songs of the Enbera people in Bogotá (Altre Modernità, 2024)
In the framework of studies on the contemporary processes of redefinition of indigenous narratives in Latin America, this paper investigates a series of artistic performances, literary and oralitegraphic proposals carried out by members of the displaced Embera people in Bogotá, with a particular focus on the context of the experience of community stay in the Olaya Herrera National Park (2021-2022). After going through some nodes of contact between urban imaginaries and contemporary indigenous epistemologies, the essay explores some Embera cultural productions, in a perspective of interpretation of indigenous creators as "embodied territories" (Rojas-Sotelo). Within the framework of the political and cultural struggle of the Embera, the essay aims to identify the trajectories of epistemic reconfiguration of their own knowledge as a result of forced displacement and the consequent symbolic re-elaborations of the imaginaries of the urban space of Bogota.
Keywords: urban indigenous people; Embera culture and literature; Colombian oralitegraphies; forced displacement; Embera in Bogotá (Colombia)